Anion transport in dog, cat, and human red cells. Effects of varying cell volume and Donnan ratio (The Rockefeller University Press, 1979)
Membrane potential and the rate constants for anion self-exchange in dog, cat, and human red blood cells have been shown to vary with cell volume. For dog and cat red cells, the outward rate constants for SO4 and Cl increase while the inward rate constant for SO4 decreases as cells swell or shrink. These changes coincide with the membrane potential becoming more negative as a result of changes in cell volume. Human red cells exhibit a similar change in the rate constants for SO4 and Cl efflux in response to cell swelling, but shrunken cells exhibit a decreased rate constant for SO4 efflux and a more positive membrane potential. Hyperpolarization of shrunken dog and cat red cells is due to a volume-dependent rate constant for SO4 efflux and a more positive membrane potential. Hyperpolarization of shrunken dog and cat red cells is due to a volume-dependent increase in PNa. If this increase in PNa is prevented by ATP depletion or if the outward Na gradient is removed, the response to shrinking is identical to human red cells. These results suggest that the volume dependence of anion permeability may be secondary to changes in the anion equilibrium ratio which in red cells is reflected by the membrane potential. When the membrane potential and cell volume of human red cells were varied independently by a method involving pretreatment with nystatin, it was found that the rate of anion transport (for SO4 and Cl) does not vary with cell volume but rather with membrane potential (anion equilibrium ratio); that is, the rate constant for anion efflux is decreased and that for influx is increased as the membrane potential becomes more positive (internal anion concentration increases) while the opposite is true with membrane hyperpolarization (a fall in internal anion concentration).